Fabrication of spherical diamond microshells - Lee, Jae-Kap; Anderson, Michael W.; Gray, Fraser A.; John, Phillip (ELSEVIER SCIENCE SA, 2007)
Spherical and hollow diamond microspheres have been fabricated by plasma coating diamond layers onto sacrificial porous silica spheres with subsequent chemical etching of the matrices. The diamond coatings have controllable micron scale apertures created by the coalescence of the contiguous diamond crystallites. Subsequent capillary-enhanced etching produced hollow diamond microspheres. The diamond microshell walls contain submicron scale channels which provided a route to rapid silica etching. The wall thickness is controllable in the range of 5%-20% of the shell diameter by control of the nucleation density and plasma deposition time. The diameters of the diamond microshells lie in the range between 30 pin and 40 gm. The diamond shells have been characterized by field emission scanning electron microscopy (FESEM) and by Raman spectroscopy. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: MICROSPHERES